Lysine Acetyltransferases and Their Role in AR Signaling and Prostate Cancer - Jaiswal, Bharti; Agarwal, Akanksha; Gupta, Ashish (Frontiers in Endocrinology, 2022)
The development and growth of a normal prostate gland as well as its physiological functions are regulated by the actions of androgens through androgen receptor (AR) signaling, that drives multiple cellular processes including transcription, cellular proliferation and apoptosis in prostate cells. Post-translational regulation of AR plays a vital role in directing its cellular activities via modulating its stability, nuclear localization and transcriptional activity. Among various post-translational modifications (PTMs), acetylation is an essential PTM recognized in AR and is governed by the regulated actions of acetyltransferases and deacetyltransferases. Acetylation of AR has been identified as a critical step for its activation and depending on the site of acetylation, the intracellular dynamics and activity of AR can be modulated. Various acetyltransferases such as CBP, p300, PCAF, TIP60 and ARD1 that are known to acetylate AR, may directly coactivate AR transcriptional function or help to recruit additional coactivators to functionally regulate the transcriptional activity of AR. Aberrant expression of acetyltransferases and their deregulated activities have been found to interfere with AR signaling and play a key role in development and progression of prostatic diseases including prostate cancer (PCa). In this review, we summarize recent research advances aimed at understanding the role of various lysine acetyltransferases (KATs) in the regulation of AR activity at the level of post-translational modifications in normal prostate physiology as well as in development and progression of PCa. Considering the critical importance of KAT in modulating AR activity in physiological and patho-physiological context, we further discuss the potential of targeting these enzymes as a therapeutic option to treat AR-related pathology in combination with hormonal therapy.